Optimalisasi Persediaan Semen Tiga Roda Pada Toko Bangunan Tamara Di Mangkurawang Tenggarong - Hariyanto, Muhammad; Bahransyah, Bahransyah; Hermanto, Muhammad (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2018)
Abstract:The main objective of this research is to know the optimal amount of Cement inventory by using Economic order Quantity method at Tamara Shop ShopInMangkurawang in January 2018. The analytical tool used to examine the economic order quantity (EOQ), reorder point and safety stock. The data used during this study was January 2018.Based on the results of research that researchers have done to prove the hypothesis, which previously has been supported by the description on the background, the formulation of the problem and the basic theory that has been the authors pointed out the following will be submitted things as follows:The optimal order amount (EOQ) at Tamara Building Shop in Mangkurawang Tenggarong is: EOQ Cement Three Wheels as much as 256 Zak.The optimal amount of Safety Stock at Tamara Building Shop in Mangkurawang Tenggarong is: Three-Wheel Cement Safety Supplies of 36 Zak.The optimal ordering point (ROP) at Tamara Building Shop is: ROP Cement Three Wheels at the time of the remaining inventory 89 Zak.The optimal ordering frequency at Tamara Building Shop in MangkurawangTenggarong, is: Frequency of booking three cement wheels as much as 6 times a month, with the distance between orders 5 days.Â Keywords: EOQ, reorder point, safety stock, order frequency